The Pengembangan Sediaan Farmasi Berbasis Herbal dari Dondai-Sentani, Papua - Eva Susanty Simaremare; Rifky Pratama Syachputra Tahir; Musdalifa Putri Maharani; Wahyu Dwi Astuti; Rahmawati Burhanuddin; Merry Christiani Samaa; Enjelina Siregar; Prilli Anastasia Mokay; Apriani Cissyvana Paskaline; Wendy Kafiar; Warry Johannest Eybe; Teresa Sawor; Anisa Zahra Rahmani; Yuliana Rut Yabansabra (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Dondai Village, Waibu District, has several potential medicinal plants that can improve the community's economy by creating new products. Service activities through the KKN/Village Wira program aim to assist and counsel the community, especially those who want to become entrepreneurs. The implementation methods are tutorials and discussions, socialization, demonstrations or training, mentoring, evaluation, and monitoring. The results obtained show that there are five products from Dondai, namely betel leaves as aromatherapy candles, putri malu leave as paper soap or betel leaf paper soap, Chinese ketepeng leaves as soap or body wash, lantana leaves as an antiseptic or hand-sanitizer, and miana lotion. As many as 97% of people are interested in making products, and 95% are interested in marketing products. It is hoped that this program can develop creativity, community knowledge, and insight to innovate to improve the standard of living.